53.2k views
9 votes
Please provide your answer along with a step-by-step explanation!

Please provide your answer along with a step-by-step explanation!-example-1
User Airon Tark
by
4.6k points

2 Answers

3 votes

Answer:

b = -12

Explanation:

Step 1: Multiply both sides by 6.

6 - 2b /6 = 5

(6 - 2b /6) *(6) = (5)*(6)

6−2b=30

Step 2: Simplify both sides of the equation.

−2b+6=30

Step 3: Subtract 6 from both sides.

−2b+6−6=30−6

−2b=24

Step 4: Divide both sides by -2.

-2b/-2 = 24/-2

b = -12

User Nioka
by
5.0k points
11 votes

Answer:

b = -12

Explanation:


(6 - 2b)/(6) = 5

We are solving for b, so we want b alone on the left side equaling a number on the right side.

Start by multiplying both sides by 6.


6 * (6 - 2b)/(6) = 6 * 5


6 - 2b = 30

Now we subtract 6 from both sides.


6 - 2b - 6 = 30 - 6


-2b = 24

Divide both sides by -2.


(-2b)/(-2) = (24)/(-2)


b = -12

User Twomz
by
5.2k points